Eosinophilia-myalgia syndrome: selective cognitive impairment, longitudinal effects, and neuroimaging findings. Issue 5 (1st November 1997) - Armstrong, Carol; Lewis, Todd; D'Esposito, Mark; Freundlich, Bruce
Abstract : OBJECTIVE: To identify the specific nature of the neurocognitive impairments of eosinophilia-myalgia syndrome (EMS) in an unselected population, and to present longitudinal patterns. METHODS: A consecutive sample of 23 patients with EMS and 18 age and education matched control subjects were assessed on a comprehensive neuropsycho- logical battery. Longitudinal results were gathered from six patients. RESULTS: Neurocognitive impairments were found which represent a subset of deficits reported in previous group and case study reports. Deficits were limited to complex visual memory, conceptual set shifting, and attention, which suggest a selective dysexecutive syndrome. The motor slowing and verbal memory deficits previously reported were not found. Although depression, fatigue, sleep deprivation, and pain were significant symptoms, they were unassociated with deficits with the exception of an association of depression with one deficit. There was no pattern of overall decline over time in a subset of the group, although considerable heterogeneity in the longitudinal patterns of neurocognitive tests was found. Abnormalities of white matter appeared in the MRI of eight of 12 patients. CONCLUSIONS: The neurocognitive and neuroimaging findings contribute to the evidence which indicates that the neural substrate of EMS is white matter damage.